2006
DOI: 10.1002/asia.200600131
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Acetylenic Scaffolding: Extended Donor‐Substituted Perethynylated Dehydroannulenes

Abstract: Starting from (Z)-bis(N,N-diisopropylanilino)-substituted tetraethynylethene (TEE), perethynylated octadehydro[12]- and dodecadehydro[18]annulenes were prepared by oxidative Hay coupling. The dodecadehydro[18]annulene with six peripheral N,N-diisopropylanilino substituents was characterized by X-ray crystallography. Elongation of the Z-bisdeprotected TEE by Cadiot-Chodkiewicz coupling with 1-bromo-2-(triisopropylsilyl)ethyne provided a Z-configured bis(butadiyne), which after alkyne deprotection afforded under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 82 publications
0
26
0
2
Order By: Relevance
“…Importantly, silylethynyl bromides have proven to be useful starting materials for the construction of conjugated enynes. [6] To our surprise, the use of 1,4-bis(2-bromoethynyl)benzene resulted in the formation of the corresponding product 3 la in 79 % yield in one step.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Importantly, silylethynyl bromides have proven to be useful starting materials for the construction of conjugated enynes. [6] To our surprise, the use of 1,4-bis(2-bromoethynyl)benzene resulted in the formation of the corresponding product 3 la in 79 % yield in one step.…”
mentioning
confidence: 77%
“…In the presence of the Pd(OAc) 2 catalyst (5 mol %), the reaction of phenylethynyl bromide (1 a, 1.2 mmol) and 4-octyne (2 a, 1 mmol) in THF at 30 8C afforded 3 aa in a 30 % yield (entry 1). The screening of various solvents revealed that the solvent played a very important role in this reaction (entries [1][2][3][4][5][6]. Only trace amounts of the desired product 3 aa was obtained when DMSO was used (entry 2), and unsatisfactory results were obtained using toluene (entry 4).…”
mentioning
confidence: 99%
“…Figure 2 shows some of the perethynylated dehydroannulene perimeters together with their longest-wavelength absorption maxima and the first oxidation and reduction potentials obtained by cyclic voltammetry (CV) and rotating-disk voltammetry (RDV). [84][85][86][87][88][89] If not indicated otherwise, all electrochemical potentials reported in this Review were recorded in CH 2 Cl 2 (þ0.1 M n-Bu 4 NPF 6 ) and referenced against the ferricinium/ ferrocene (Fc þ /Fc) couple as internal standard. The chargetransfer character of the longest-wavelength absorption maximum in the UV-vis spectra of donor-acceptor systems was confirmed by protonation (disappearance of the band) and reneutralization (reappearance of the band).…”
Section: Perethynylated Dehydroannulenesmentioning
confidence: 99%
“…The product was cross-coupled to 4-iodobenzonitrile (0.060 g, 0.26 mmol) in deoxygenated THF (5 mL) in the presence of Pd(PPh 3 ) 4 (0.008 g, 0.007 mmol), iPr 2 NH (2 mL), and CuI (0.0025 g, 0.013 mmol) at 40−50°C for 18 h. The reaction was cooled to rt, Et 2 O (10 mL) and H 2 O (5 mL) were added, the organic phase was separated, washed with saturated aq NH 4 Cl (2 × 50 mL) and brine (2 × 50 mL), dried (MgSO 4 ), and filtered, and the solvent was removed in vacuo. Flash column chromatography (silica gel CH 2 Cl 2 /hexanes 3:10 → 1:1) followed by precipitation from hexanes afforded compound 27 (0.091 g, 57% from 13) as a yellow solid: mp 114−116°C (discolors, dec); R f = 0.37 (EtOAc/hexanes 3:17); UV−vis (CH 2 Cl 2 ) λ max (ε) 448 (30900), 332 (63400), 250 (49600) 20) provided the crude terminal diyne (ca. 0.08 g, ca.…”
Section: ■ Conclusionmentioning
confidence: 99%